TRPV4 Channel in Neurological Disease: from Molecular Mechanisms to Therapeutic Potential - Feng Zhang; Hritik Mehta; Hadi Hasan Choudhary; Rezwanul Islam; Khalid A. Hanafy (Molecular Neurobiology, 2025)
Transient Receptor Potential Vanilloid 4 (TRPV4) is a non-selective cation channel with pivotal roles in various physiological processes, including osmosensitivity, mechanosensation, neuronal development, vascular tone regulation, and bone homeostasis in human bodies. Recent studies have made significant progress in understanding the structure and functional role of TRPV4, shedding light on its involvement in pathological processes, particularly in the realm of neurological diseases. Here, we aim to provide a comprehensive exploration of the multifaceted contributions of TRPV4 to neurological diseases, spanning its intricate molecular mechanisms to its potential as a target for therapeutic interventions. We delve into the structural and functional attributes of TRPV4, scrutinize its expression profile, and elucidate the possible mechanisms through which it participates in the pathogenesis of neurological disorders. Furthermore, we discussed recent years’ progress in therapeutic strategies aimed at harnessing TRPV4 for the treatment of these diseases. These insights will provide a basis for understanding and designing modality-specific pharmacological agents to treat TRPV4-associated disorders.